Energy Supply to Buses on a Conductive Electric Road: An Evaluation of Charger Topologies and Electric Road Characteristics - Anton Karlsson; Mats Alaküla (World Electric Vehicle Journal, 2021)
An electric road system (ERS) enables transfer of electric energy to a moving vehicle, making it possible to reduce the capacity—and cost—of the battery and the need for static chargers. A conductive electric road allows for relatively low complexity whilst being able to provide high levels of power. When utilising a conductive electric road, safety precautions must be considered with regard to isolation between the charging supply (the electric road) and the vehicle’s traction voltage system (TVS), since no protective Earth connection can be guaranteed. Isolation can be achieved by separating the two systems galvanically or by double isolating the entire TVS and all equipment connected to it on-board the vehicle. This study used the experimental results from a previous paper to model and evaluate three different electric powertrains/charger topologies, including a novel integrated design fulfilling the required safety features. The models were used in a full vehicle model and further investigated in a city bus scenario in terms of how charging performance, energy consumption and battery ageing are affected by the aforementioned charging topologies and electric road characteristic. We discovered that charging topology has a strong influence on energy consumption, and that electric road characteristics have a strong influence on battery ageing.